ANALISIS PERWILAYAHAN KOMODITAS SEMANGKA DI KABUPATEN BANYUWANGI - Yunita Mayangsari; Aryo Fajar Sunartomo (JSEP (Journal of Social and Agricultural Economics), 2021)
Watermelon commodity has the highest productivity compared to other superior fruit commodities in Banyuwangi Regency. However, the land area and production of watermelon commodities are still quite volatile and their distribution is uneven. Therefore, a regional approach for watermelon commodities is needed in Banyuwangi Regency. This study aimed to determine the watermelon commodity base area, the characteristics of the watermelon commodity distribution, and the carrying capacity of the watermelon commodity on fruit horticultural crops in the Banyuwangi Regency. The determination of the research area was carried out intentionally in Banyuwangi Regency. The analytical methods used were Location Quotient (LQ) analysis, localization and specialization analysis, as well as Basic Service Ratio (BSR) and Regional Multiplier (RM) analysis. The results of the analysis show that the sub-district area was the basis for watermelon commodities in Banyuwangi Regency. The characteristics of the distribution of watermelon commodities in the Banyuwangi Regency were not localized. Watermelon farming activities are not concentrated in one sub-district but spread to several sub-districts in Banyuwangi Regency. The results of the analysis of the Basic Service Ratio (BSR) and Regional Multiplier (RM) of watermelon commodities produce more than one value. The existence of watermelon commodity farming activities can support fruit horticultural farming activities in Banyuwangi Regency.